Prosedur Serah Terima Tugas Sebelum Crew Melaksanakan Dinas Jaga Di Kapal KM. Sabuk Nusantara - Dedi Nuryaman; Shela Denisyanti (LPPM AKMI SUAKA BAHARI CIREBON, 2022)
The role of sea transportation is one of the important modes of transportation. Especially the export-import activities of goods that generate foreign exchange. Therefore, sea transportation facilities for the distribution of goods are the main alternative. In order for this to be carried out properly, it takes the skill of officers to carry ships safely, accompanied by a sense of responsibility and a high work ethic. The rules of guard duty that have been set must be carried out without exception, in order to prevent dangers both while sailing and docking. Research with this descriptive technique is collected in the form of words with the results of observations, interviews, field notes, photos, video tapes, personal documents, notes or memos, and other official documents from research in KM. SABUK NUSANTARA 35. Where the duty of care is carried out well by the guard officers and crew, however, there are things that prevent it from being carried out, namely violations of procedures, workload, and crew fitness. Then carry out the handover of a good guard duty, but in its implementation it is still not optimal. The steps taken to maximize its implementation are preparation, implementation of standards, and implementation.